Case Report: A novel intronic variant of NIPBL gene detected in a child with cornelia de lange syndrome - Shao, Xiao Ting; Dai, Yu Xuan; Zhao, Yu Fang; Chen, Yu Hang; Ying, Ling Jing (Frontiers in Genetics, 2025)
BackgroundCornelia de Lange syndrome (CdLS) is a genetically heterogeneous disorder involving multi-system organs, causing physical and mental congenital malformation. Nipped-B-like protein (NIPBL) variants are associated with various CdLS phenotypes. Newborns with typical clinical manifestations (intellectual disability, special appearances, and limb malformation) require a diagnosis. However, diagnosing CdLS is challenging on account of its heterogeneity of genotype and phenotype.MethodsIn this study, molecular analysis was applied, containing whole exome sequencing (WES), reverse transcriptase PCR (RT-PCR), and minigene splicing assays.ResultsWe identified a novel splice-donor variant (NIPBL c.6343 + 1G>A) by WES. RT-PCR and minigene splicing assays were performed to identify the function of the splice-donor variant on subsequent RNA splicing. The variant caused exon 36 to be skipped. A premature termination codon (PTC) appeared subsequently and a truncated protein with a length of 2088 aa was produced.ConclusionA novel pathogenic variant of CdLS is identified, which affects normal mRNA splicing of the NIPBL gene. These findings enrich the knowledge of CdLS gene variants, which may be responsible for developing this rare disease.